Habituation Model of Arabic Learning in Modern Islamic Boarding School: A Case Study of Pondok Modern Darussalam Gontor - Setiawan, Andry; Husain, Andi Musthafa; Bahri, Saiful (el-Tarbawi, 2023)
Acquiring proficiency in Arabic as a non-Arabic native requires effort and constant practice for the language to become carved in the individual's linguistic repertoire. This inquiry aims to analyze and describe in depth the following efforts to familiarize the Arabic language in Gontor. It discusses how Pondok Modern Darussalam Gontor applies the Arabic habituation model for understanding Arabic literacy, which discusses the methods, systems, roles of each element, and the results of the habituation. This study employs a qualitative approach that includes direct observation, interviews, and documentation. The findings revealed that the Arabic habituation model in Gontor was carried out systematically, using a direct technique, and that diverse activities and a conducive atmosphere were built in it to promote the habituation, and that every element of the Gontor played a role in generating an optimal language milieu.